The ‘subject’ of Freeman & Johnson’s reconceived knowledge base of second language teacher education - Cross, Russell (Language teaching research : LTR, 2020)
This article focuses on reframing the ‘who’ of second language teacher education (SLTE), building on the framework laid out by Freeman and Johnson (FJ) in 1998 with particular attention to their notion of the teacher-as-learner. The first half of this article is conceptual, outlining one way I have found helpful for engaging with this notion since first encountering the framework some twenty years ago. The second half, being more substantive in focus, risks misinterpretation without this broader perspective: propositional ‘who’s’ that lack relevance on their own, not least in the way I see FJ’s call to engage with ‘the who of teaching’, and a focus on not just the individual, but also the context, goals, and background from which one comes to take up that role. This includes a discussion of the teacher-subject as an increasingly communicatively-complex, conflicted-compliant, and collaboratively-creative agent within the kinds of spaces that their roles can be realized against emerging contexts for ELT.